Comparative Study of Hydro-Magneto-Electric Regenerative Shock Absorber (HMERSA) with Two Outputs Hydraulic Generator Installed Series And Parallels - Taufik Kurniawan; Harus Laksana Guntur (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2021)
Through the Regenerative Shock Absorber (RSA) mechanism, wasted energy will be utilized into electrical energy. Hydro-Magneto-Electric Regenerative Shock Absorber (HMERSA) was designed and analyzed with 2 generator outputs installed in series and parallel. The twin-tube shock absorber was modified, so that fluid flow in the chamber is only unidirectional flow. It is passed to four check valves that keep the fluid flow in one direction and towards the 2 hydro-generators installed on the system in series and parallel positions. The hydro-generator converts the linear fluid flow into a rotational motion which causes the generator to rotate and generate energy. HMERSA was tested on minibus with speed bumps types of roads. In the bump test, the harvested energy were 8.2 Volts and 5.97 Volts for HMERSA with 2 generator outputs installed in series, and 5.169 Volts and 4.33 Volts for HMERSA with 2 parallel output generators. From the result, we can conclude that HMERSA with 2 generator outputs installed in series is better than HMERSA with 2 parallel output generators.